2005
DOI: 10.1039/b411516c
|View full text |Cite
|
Sign up to set email alerts
|

Localized electrosynthesis of polypyrrole by application of short voltage pulses

Abstract: By the application of short voltage pulses to a tool electrode in close proximity to a substrate electrode, the electro-polymerization of pyrrole in aqueous solution was locally confined with down to micrometer precision. Depending on the pulse parameters polypyrrole towers with up to 100 microm height and about 50 microm diameter were fabricated on the substrate. The spatial confinement of the electro-polymerization reaction is explained by the local charging behavior of the double layer capacitance during vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…This becomes even more important upon the electrodeposition of conductive polymers like polypyrrole, where the polymer precipitates from solution and mass transport in the tool-workpiece gap is of relevance. [26]…”
Section: Machinable Materialsmentioning
confidence: 99%
“…This becomes even more important upon the electrodeposition of conductive polymers like polypyrrole, where the polymer precipitates from solution and mass transport in the tool-workpiece gap is of relevance. [26]…”
Section: Machinable Materialsmentioning
confidence: 99%
“…14 Furthermore, PP nanowires or microtubules have been synthesized by electrochemical polymerization with a scanning microneedle as an electrode 15 or application of short voltage pulses. 16 All of these methods require a rather tedious postdeposition process for removal of the template to release the micro-and nanostructured polymers. 17 Recently, Qu et al 18 and others 19 -21 have reported the electrochemical deposition of template-free PPy microcontainers onto 'soap bubbles' associated with O 2 released from electrolysis of water (H 2 O) in an aqueous solution ofˇ-naphthalenesulfonic acid (ˇ-NSA), which acts as both surfactant and electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining well defined 3D structures remains rather difficult and has been mainly obtained via deposition of films in template structures [5]. Recently, rapid pulse electrodeposition, an electrochemical technique which allows the 3D patterning of electrochemically active materials with sub micrometer precision, has been introduced [6].…”
Section: Introductionmentioning
confidence: 99%
“…Because the rates of electrochemical reactions are exponentially dependent on the potential drop in the DL, the reactions are strongly confined to these polarized electrode regions in very close proximity. This method contrasts with conventional electroforming methods, in which the application of DC voltage causes uniform DL charging and the reaction rate is mainly defined by the current density in the electrolyte, thus enabling only limited spatial resolution of about 0.1 mm [5,6]. The parameters of pulsed electrodeposition are the pulse length (t on ), the time between two pulses (t off ), the peak height (I pulse ), and the average current density (I a ).…”
Section: Introductionmentioning
confidence: 99%